Transducer Development and Modeling for Mass Air Flow Sensor - A. Kryukov, Yu.; A. Mikheev, M; Ð¢.Ð•., Golovchenko; V. Ivanov, V; S. Vorontsov, I (International Journal of Engineering and Technology, 2018)
The article describes the development of the computer model and the modeling of mass air flow sensor using SolidWorks and ANSYS software. Using SolidWorks, a three-dimensional model of a mass air flow sensor was created, then this model was transferred to the ANSYS software complex, where transducer functioning process was modeled by finite element method. Several variants of sensor transducer elastic element geometry were considered and an optimal design was chosen.Â Â Â